The Use of English Pronunciation Application as a Supporting Media in Enhancing Students’ Pronunciation (Conference on English Language Teaching, 2024)
In an era characterized by the ubiquitous integration of technology in education, effective communication is essential, and the English language has risen as the common language uniting individuals with varied backgrounds. Pronunciation, a fundamental aspect of language proficiency, plays a crucial role in effective communication. This study explores the impact of integrating an innovative pronunciation application into the learning experiences of students. Through a quantitative approach and data collection from a structured questionnaire, focusing on the dynamic context of English Education Major at UIN Prof. K.H. Saifuddin Zuhri Purwokerto, this study seeks to investigate the efficacy and practical implications of employing an English Pronunciation Application as a supporting media in the enhancement of students' pronunciation skill. The findings suggest that the English Pronunciation Application has been successful in serving as a supportive media, leading to significant improvement in students’ pronunciation abilities.